Flat detector computed tomography angiography with intravenous contrast application: Feasibility for visualization of cerebral arterial vasculature - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Ott, Sabine; Struffert, Tobias; Dörfler, Arnd (Journal of Neuroimaging, 2013)
BACKGROUND AND PURPOSE: The aim of our study was to evaluate flat detector computed tomography angiography with peripheral intravenous contrast material application (FD-CTA) for visualization of cerebral arteries in comparison with intravenous multidetector computed tomography angiography (CTA) and intraarterial digital subtraction angiography (DSA). METHODS: The study was approved by the local institutional review board and informed consent was obtained by all participants. Ten patients underwent FD-CTA, CTA, and DSA of the cerebral arterial vasculature for suspected cerebrovascular disease. The image data were evaluated by two readers in consensus for the visualization of cerebral arterial segments on a 5-point scale (0 = vessel cannot be distinguished; 4 = excellent image quality). The Wilcoxon signed-rank test was used for statistical analysis. Note that P < .05 was considered to indicate a significant difference. RESULTS: The depiction of cerebral arterial segments with FD-CTA was significantly superior compared to CTA in most vessel segments (P < .05 in 20 of 23 anatomic regions) and was without significant difference compared with DSA in large and medium intracranial vessels. CONCLUSIONS: The results suggest that the cerebral arteries can be visualized by FD-CTA in high resolution, in many vessel segments comparable to DSA. © 2012 by the American Society of Neuroimaging.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Cerebral; Computed tomography; Flat detector; Intravenous